Current application status of pelvic rrgan resection in locally advanced rectal cancer and local recurrent rectal cancer - Lu Li; Ren Donglin (结直肠肛门外科, 2022)
Pelvic organ resection is currently considered a selective salvage surgery for some patients with locally advanced rectal cancer and local recurrent rectal cancer. However, due to the extensive resection range, the high incidence of complications, and the high perioperative mortality rate, the promotion of this surgical procedure has been limited. In recent years, the advancement of surgical equipment, instruments, and related technologies, along with the enhancement of perioperative management and monitoring treatments, has reduced the incidence of complications and mortality in patients undergoing pelvic organ resection. Moreover, this procedure significantly extends the tumor-free survival period for patients with locally advanced rectal cancer and local recurrent rectal cancer, and can be recommended as a radical surgical technique for suitable patients. This paper reviews the current application status and related hot topics of pelvic organ resection in locally advanced rectal cancer and local recurrent rectal cancer.